1) a) ( 3x + y – z ) – ( 4x – 2y + 6z ) b) K=2x × ( -3x + 5 ) + 3x × ( 2x – 12 ) + 26x

Question

1)
a) ( 3x + y – z ) – ( 4x – 2y + 6z )
b) K=2x × ( -3x + 5 ) + 3x × ( 2x – 12 ) + 26x

in progress 0
Melanie 4 ngày 2021-09-10T12:25:14+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-09-10T12:26:36+00:00

    Đáp án: $a,$ $=-x+3y-7z$

                $ b,$ $=0$

     

    Giải thích các bước giải:

    $a)(3x+y-z )-(4x-2y+6z)$

    $=3x+y-z-4x+2y-6z$

    $=-x+3y-7z$

    $b, K=2x(-3x+5 )+3x(2x-12)+26x$

    $=-6x+10x+6$$x^{2}$ $-36x+26x$

    $=$$-6$$x^{2}$$+10x +6x^{2} -36x+26x$

    $=0$

     

    0
    2021-09-10T12:27:01+00:00

    $a) (  3x + y – z ) – ( 4x – 2y + 6z )\\=3x+y-z-4x+2y-6z\\=-x+3y-7z\\b) K=2x . ( -3x + 5 ) + 3x . ( 2x – 12 ) + 26x\\K=-6x^{2}+10x+6x^{2}-36x+26x=0$

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )